Perspective: Challenges Presented for Regeneration of Heterogeneous Musculoskeletal Tissues that Normally Develop in Unique Biomechanical Environments - Hart, David A.; Nakamura, Norimasa; Shrive, Nigel G. (Frontiers in Bioengineering and Biotechnology, 2021)
Perspective: Musculoskeletal (MSK) tissues such as articular cartilage, menisci, tendons, and ligaments are often injured throughout life as a consequence of accidents. Joints can also become compromised due to the presence of inflammatory diseases such as rheumatoid arthritis. Thus, there is a need to develop regenerative approaches to address such injuries to heterogeneous tissues and ones that occur in heterogeneous environments. Such Injuries can compromise both the biomechanical integrity and functional capability of these tissues. Thus, there are several challenges to overcome in order to enhance success of efforts to repair and regenerate damaged MSK tissues. Challenges: 1. MSK tissues arise during development in very different biological and biomechanical environments. These early tissues serve as a template to address the biomechanical requirements evolving during growth and maturation towards skeletal maturity. Many of these tissues are heterogeneous and have transition points in their matrix. The heterogeneity of environments thus presents a challenge to replicate with regard to both the cells and the ECM. 2. Growth and maturation of musculoskeletal tissues occurs in the presence of anabolic mediators such as growth hormone and the IGF-1 family of proteins which decline with age and are low when there is a greater need for the repair and regeneration of injured or damaged tissues with advancing age. Thus, there is the challenge of re-creating an anabolic environment to enhance incorporation of implanted constructs. 3. The environments associated with injury or chronic degeneration of tissues are often catabolic or inflammatory. Thus, there is the challenge of creating a more favorable in vivo environment to facilitate the successful implantation of in vitro engineered constructs to regenerate damaged tissues. Conclusions: The goal of regenerating MSK tissues has to be to meet not only the biological requirements (components and structure) but also the heterogeneity of function (biomechanics) in vivo. Furthermore, for many of these tissues, the regenerative approach has to overcome the site of injury being influenced by catabolism/inflammation. Attempts to date using both endogenous cells, exogenous cells and scaffolds of various types have been limited in achieving long term outcomes, but progress is being made.